NOX2 Deficiency Permits Sustained Survival of S. aureus in Macrophages and Contributes to Severity of Infection - Tosetti, Bettina; Ward, Beate; Grumme, Daniela; Herb, Marc; Schramm, Michael; Utermöhlen, Olaf; Heukamp, Lukas C.; Krönke, Martin; Krut, Oleg (Frontiers in Immunology, 2021)
Although the crucial role of professional phagocytes for the clearance of S. aureus infections is well established, several studies indicate an adverse role of leukocytes in the dissemination of S. aureus during infection. Since only little is known about macrophages in this context, we analyzed the role of macrophages, and in particular reactive oxygen species deficiency, for the seeding of S. aureus metastases. Infection of bone marrow-derived macrophages (BMDM) with S. aureus revealed that NADPH oxidase 2 (NOX2-) deficient, but not NOX1- or NOX4-deficient, BMDM failed to clear intracellular S. aureus. Despite of larger intracellular bacterial burden, NOX2-deficient BMDM showed significantly improved survival. Intravenous injection of mice with in vitro-infected BMDMs carrying intracellular viable S. aureus led to higher bacterial loads in kidney and liver of mice compared to injection with plain S. aureus. An even higher frequency of liver abscesses was observed in mice infected with S. aureus-loaded nox2-/- BMDM. Thus, the improved intracellular survival of S. aureus and improved viability of NOX2-deficient BMDM is associated with an aggravated metastatic dissemination of S. aureus infection. A combination of the vancomycin and the intracellularly active antibiotic rifampicin led to complete elimination of S. aureus from liver within 48 hours, which was not achieved with vancomycin treatment alone, underscoring the impact of intracellular S. aureus on the course of disease. The results of our study indicate that intracellular S. aureus carried by macrophages are sufficient to establish a systemic infection. This suggests the inclusion of intracellularly active antibiotics in the therapeutic regimen of invasive S. aureus infections, especially in patients with NADPH oxidase deficiencies such as chronic granulomatous disease.